2019
DOI: 10.12659/msm.915507
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Mechanical Ventilation Combined with Fiberoptic Bronchoalveolar Lavage in Patients with Severe Pulmonary Infection

Abstract: Background The aim of this study was to assess the clinical efficacy and safety of mechanical ventilation combined with fiberoptic bronchoalveolar lavage in patients with severe pulmonary infection. Material/Methods We randomly divided 81 patients with severe pulmonary infection into a control group (n=40) and an observation group (n=41). Both groups were treated using mechanical ventilation, and observation group additionally received assistive fiberoptic bronchoalveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The establishment of an artificial airway in an ICU patient results in the disappearance of the natural barrier of the upper respiratory tract and direct communication of the lower respiratory tract with the outside air. Various invasive medical procedures potentially increase the risk of infection in the lower respiratory tract [28]. The establishment of the artificial airway opens the respiratory pathway for the patient, but long-term mechanical ventilation and open-ended invasive procedures such as suction and fiberoptic bronchoscopy increase the incidence of VAP [29].…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of an artificial airway in an ICU patient results in the disappearance of the natural barrier of the upper respiratory tract and direct communication of the lower respiratory tract with the outside air. Various invasive medical procedures potentially increase the risk of infection in the lower respiratory tract [28]. The establishment of the artificial airway opens the respiratory pathway for the patient, but long-term mechanical ventilation and open-ended invasive procedures such as suction and fiberoptic bronchoscopy increase the incidence of VAP [29].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the application of high-dose AH significantly improves the therapeutic effect on pulmonary infection without obvious adverse reactions [ 15 ]. BAL with a bronchoscope can directly enter the diseased region and remove inflammatory secretions in the region, thus reducing airway resistance and respiratory consumption, increasing the blood oxygenation level of the pulmonary alveolus, and improving pulmonary function [ 16 ]. In our study, AH can directly reach the diseased region through BAL, further improving the efficiency of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that B-ACT could improve some important laboratory results including some inflammatory factors (CRP and PCT), routine blood parameters (WBC# and N%) and blood gas analysis (PO 2 and SO 2 ). Consistent with our results, a retrospective study admitting 81 SP patients with IMV reported that not only inflammation indicators including tumor necrosis factor-a (TNF-α), CRP, IL-8 and IL-6 but also blood gas indexes including PO 2 and SO 2 were significantly better in the bronchoalveolar lavage (BAL) group than those in the control group after bronchoscopy, in which hospital stay, IMV time, and infection control window appearance time in the observation group were significantly shorter than those in the control group after bronchoscopy (all p < 0.05) [15]. Moreover, a prospective study enrolling 103 SP patients including patients with IMV demonstrated that the changes of APACHE II scores, inflammatory indicators (CRP, TNF-αand PCT) and blood gas analysis (oxygenation index (OI), PO 2 and SO 2 ) in the bronchoscopy group were more pronounced than those in the control group after treatment, and the length of stay in ICU, IMV time and duration of antibiotics of the bronchoscopy group were shorter than those of the control group after treatment (all p < 0.05) [16].…”
Section: Discussionmentioning
confidence: 99%